2021
DOI: 10.1016/j.annonc.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal tracking of 97 esophageal adenocarcinomas using liquid biopsy sampling

Abstract: Background: The incidence of esophageal adenocarcinoma (EAC) is rapidly rising and has a 5-year survival rate of <20%. Beyond TNM (tumorenodeemetastasis) staging, no reliable risk stratification tools exist and no large-scale studies have profiled circulating tumor DNA (ctDNA) at relapse in EAC. Here we analyze the prognostic potential of ctDNA dynamics in EAC, taking into account clonal hematopoiesis with indeterminate potential (CHIP). Patients and methods: A total of 245 samples from 97 patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 32 publications
8
93
0
Order By: Relevance
“…When analyzing the 31 samples collected postsurgery, we demonstrated that 70% of patients with a FrEIA score above the detection threshold (13 out of 18 patients) developed a recurrence. Our results are comparable to mutation-based detection of tumor-derived cfDNA in resectable EAC (7,8). In a recent publication a ctDNA panel consisting of 77 genes was tested in 97 EAC patients.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…When analyzing the 31 samples collected postsurgery, we demonstrated that 70% of patients with a FrEIA score above the detection threshold (13 out of 18 patients) developed a recurrence. Our results are comparable to mutation-based detection of tumor-derived cfDNA in resectable EAC (7,8). In a recent publication a ctDNA panel consisting of 77 genes was tested in 97 EAC patients.…”
Section: Discussionsupporting
confidence: 72%
“…In a recent publication a ctDNA panel consisting of 77 genes was tested in 97 EAC patients. After filtering of CHIP variants, the panel showed high prognostic potential for disease-free survival (HR 5.35, 95% CI 2.10-13.63; P ≤ 0.0001) based on the post-surgery samples (7). Another paper used an EAC tumor guided sequencing approach and found ctDNA status (positive vs. negative) to be prognostic at baseline for disease-free survival (p=0.042) (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, growing evidence suggests a higher benefit of ICB-therapies in circulating tumor DNA (ctDNA)-positive patients in several malignancies, with a favorable prognostic role of ctDNA seroconversion rates ( 177 ) ( 178 ). Consolidated data concerning eventual prognostic/predictive roles of this biomarker could possibly instruct for the use of ctDNA seroconversion rate as a primary endpoint of (neo)adjuvant CV clinical trials, alongside long-term survival data (i.e.…”
Section: Introductionmentioning
confidence: 99%